DISINFORMATION AND DIGITAL ELECTORAL CRIMES: CHALLENGES FOR DEMOCRACY (CIPEEX, 2025)
This study analyzes disinformation and digital electoral crimes as challenges to contemporary democracy, with an emphasis on combating fake news and the use of artificial intelligence in electoral campaigns. The objective was to understand how the spread of false information and the use of digital technologies affect the integrity of the Brazilian electoral process. The method used was bibliographical and documentary research, based on legislation, Superior Electoral Court resolutions, and recent academic works on the topic. The results indicated that disinformation compromises the free formation of voters' will, intensifies political polarization, and favors illicit practices. While artificial intelligence, while representing innovation in campaigns, can enhance content manipulation through deepfakes and mass messaging. The conclusion is that effectively addressing this phenomenon requires a combination of regulatory measures, firm action by the Electoral Court, accountability on the part of digital platforms, and media literacy policies, ensuring the protection of democracy in the digital age.
Keywords: democracy; fake news; artificial intelligence; disinformation